Impact on Prognosis of the Surgical Route, Laparoscopy or Laparotomy, for the Surgical Staging of Early Stage Ovarian Cancer—A Study from the FRANCOGYN Group - Margaux Merlier (Journal of Clinical Medicine, 2020)
Background and objective: according to the latest ESMO−ESGO recommendations, laparotomy is the standard surgical approach to treat and stage patients with presumed early stage epithelial ovarian cancer (EOC). A few studies have investigated the efficacy and the safety of laparoscopy for the staging of early stage EOC, and this question is still in the center of debates. Recurrence-free survival (RFS) and overall survival (OS) benefits of the minimally invasive surgery (MIS) have still to be specified. The aim of this multicenter and retrospective study is to assess the survival outcomes of laparoscopic staging in comparison with laparotomic staging for patients presenting with an early stage EOC. Methods: data of patients with early stage EOC (FIGO I-IIA) who underwent primary surgery between 2000 and 2018 were extracted from the FRANCOGYN database. OS and RFS of these two groups, constituted according to the surgical route, were compared using Log rank test. Results: of the 144 patients included, 107 patients underwent laparotomy and 37 underwent laparoscopy for a staging purpose. The median follow-up was 36.0 months (18.0 to 58.0). For the laparoscopy and the laparotomy group, the median follow-up period was 24 (11.0 to 50.0) and 42.0 (24.0 to 66.0) months, respectively, (p < 0.001). Tumor recurrence occurred in 33 (23%) patients: 2 (5.4%) in the laparoscopy group and 31 (29%) in the laparotomy group (p = 0.08). The OS rate at 5 years was 97.3% after laparoscopy and 79.8% after laparotomy (p = 0.19). Conclusions: there is no difference associated with the laparoscopic approach for the staging of early stage EOC on RFS and OS in comparison with laparotomy. MIS may be proposed as a safe and adequate alternative to laparotomy when performed by well-trained surgeons.